2022
DOI: 10.1039/d2sc02767d
|View full text |Cite
|
Sign up to set email alerts
|

Heterostructured FeNi hydroxide for effective electrocatalytic oxygen evolution

Abstract: Hydrogen production technology by water splitting has been heralded as an effective means to alleviate the envisioned energy crisis. However, the overall efficiency of water splitting is limited by the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The Fe 2p spectrum (Figure b) could also be resolved into Fe 3+ and Fe 2+ states for the 2p 3/2 and 2p 1/2 spin components, respectively, which shows a small positive shift of the strong peak at 712.78 eV for the composite compared with that of the pure NiFe-LDH at a binding energy of 712.48 eV, revealing an increased valence state of Fe . It is reported that the high valence of Fe and Ni sites helps strengthen the binding with OH – to promote the formation of the oxygen-containing intermediates (*OH, *O, and *OOH), and thus accelerating the OER reaction kinetics. The O 1s spectrum of NiFe-LDH/SnS also exhibits a small positive shift of ∼0.2 eV with respect to that of pure NiFe-LDH, as shown in Figure c. In contrast, the binding energy of the Sn 3d spin–orbits in the NiFe-LDH/SnS composite (Figure d) exhibits a negative shift of approximately 0.2 eV relative to that of the pure SnS.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The Fe 2p spectrum (Figure b) could also be resolved into Fe 3+ and Fe 2+ states for the 2p 3/2 and 2p 1/2 spin components, respectively, which shows a small positive shift of the strong peak at 712.78 eV for the composite compared with that of the pure NiFe-LDH at a binding energy of 712.48 eV, revealing an increased valence state of Fe . It is reported that the high valence of Fe and Ni sites helps strengthen the binding with OH – to promote the formation of the oxygen-containing intermediates (*OH, *O, and *OOH), and thus accelerating the OER reaction kinetics. The O 1s spectrum of NiFe-LDH/SnS also exhibits a small positive shift of ∼0.2 eV with respect to that of pure NiFe-LDH, as shown in Figure c. In contrast, the binding energy of the Sn 3d spin–orbits in the NiFe-LDH/SnS composite (Figure d) exhibits a negative shift of approximately 0.2 eV relative to that of the pure SnS.…”
Section: Resultsmentioning
confidence: 91%
“…The calculation results are well consistent with the electronic structure regulation caused by the incorporation of SnS, as analyzed for the oxidation states of Ni, Fe in the XPS spectra. The Sn atom in the SnS attracts electrons from the Ni and Fe sites and increases the valence of the Ni and Fe sites, lowering the Gibbs free energy change of the reaction process and thus enhancing the catalytic activity. …”
Section: Resultsmentioning
confidence: 99%
“…The peak corresponding to C–OH was absent in CoFe-LDH as the carbon support was absent in this material (Figure S7a, SI). The Fe 2p spectrum has been fitted into two pairs of peaks, corresponding to Fe 3+ (712.3 and 724.4 eV) and two satellite peaks at 717.5 and 733.0 eV (Figures b and S7b, S8b, S9b, SI). , Co 2p spectra revealed two peaks at 780.6 and 782.7 eV for Co 3+ 2p 3/2 and Co 2+ 2p 3/2 , respectively (Figures c and S7c, S8c, S9c, SI) . The spin–orbit coupling peaks were located at 796.6 and 797.8 eV for Co 3+ 2p 1/2 and Co 2+ 2p 1/2 , respectively (Figures c and S7c, S8c, S9c, SI) .…”
Section: Resultsmentioning
confidence: 94%
“…[1][2][3][4] Hydrogen energy is regarded as a friendly alternative to traditional fossil fuels due to its wide range of sources and high energy density and water being the only combustion product. [5][6][7][8] Water electrolysis technology is considered the most promising way to obtain hydrogen (H 2 ). 9,10 Generally, Pt-based noble metal materials are known as the ideal hydrogen evolution reaction (HER) catalysts due to the corresponding low overpotential and excellent reaction kinetics.…”
Section: Introductionmentioning
confidence: 99%